Spatiotemporal dynamics of drug‐resistant Mycobacterium tuberculosis: Contrasting trends and implications for tuberculosis control in EU high‐priority country - Mokrousov, Igor; Vyazovaya, Anna; Levina, Klavdia; Gerasimova, Alena; Zhuravlev, Viacheslav; Viiklepp, Piret; Kütt, Marge (Transboundary and emerging diseases, 2021)
Different and contrasting trends related to human migration and the implementation of health control programmes influence the spread of drug‐resistant tuberculosis (TB). We analysed the Mycobacterium tuberculosis population structure in Estonia, a high‐priority EU country for TB control, to detect the dynamic changes and underlying factors. The study collection included 278 M. tuberculosis isolates recovered in 1999 and 2014–2015. The isolates were subjected to drug susceptibility testing, genotyping and analysis of sublineage/cluster‐specific markers and drug resistance mutations. The Beijing genotype was the most prevalent, and its rate increased from 28.6% in 1999 to 38.5% in 2015 (p = .09). The non‐Beijing strains represented Euro‐American lineage (Latin American Mediterranean [LAM], Ural, Haarlem, T, X genotypes) and Indo‐Oceanic lineage (one EAI‐IND isolate). The proportion of isolates resistant to two or more drugs increased from 22.4% to 29.1% (p = .1). The pre‐XDR/XDR isolates were identified only within the Beijing genotype. In contrast, the drug resistance rate decreased in the LAM genotype from 42.1% to 11.8% (p = .05). The Beijing B0/W148‐cluster (‘successful Russian strain’) included only MDR, pre‐XDR or XDR isolates. All B0/W148‐cluster isolates were resistant to two or more drugs compared to 28% of the Beijing 94–32‐cluster (p = .0002). The Beijing genotype was not identified in the isolates from patients born in Estonia before 1940 compared to its 35.2% rate among other patients. In summary, the circulation of the highly drug‐resistant isolates of the Beijing B0/W148 subtype, the increased prevalence of the Beijing genotype among HIV‐coinfected patients and the increased number of patients with alcohol abuse (47.5%) present major challenges of the current TB control in Estonia. The Beijing genotype was likely brought to Estonia after 1945 due to the massive human influx from the Soviet Union. In contrast, the main genotypes of the Euro‐American lineage were likely endemic in Estonia during all 20th century.